Ecological and human health risks appraisal of metal(loid)s in agricultural soils: a review - Vinod Kumar; Shevita Pandita; Anket Sharma; Palak Bakshi; Pooja Sharma; Ioannis Karaouzas; Renu Bhardwaj; Ashwani Kumar Thukral; Artemi Cerda (Geology, Ecology, and Landscapes, 2021)
Agriculture is one of the major human activities that changed the landforms, water resources and the biogeochemical cycles. Pollution of agricultural soilsby metal(loid)s is a serious and global hazard but worldwide studies related to metal(loid)s pollution in agricultural soils are very limited. To fulfil this gap, metal(loid)s content in agricultural soils from 2001 to 2019 all over the world was reviewed. Multivariate statistical techniques, contamination indices and human health risk assessment were determined for the metal(loid)s. Among the analysed metal(loid)s, the average contents of Zn, Cu, Pb, Cr, Cd, As and Ni exceeded the Canadian, and China soil guidelines limits. The results of contamination factor indicated that Cr, Pb, Cd, As and Zn are the key pollution contaminants. As and Cd had the highest enrichment among the analysed metal(loid)s according to the enrichment factor. The potential and modified ecological risk index showed that Cd is the foremost contaminant responsible for ecological threats. The non-carcinogenic risk for ingestion pathway indicated that As, Pb and Cr are the foremost contaminants responsible for affecting human health, while dermal pathway results showed less risk of metal(loid)s in the agricultural soils. The carcinogenic risk revealed that As, Pb and Cr are the key contaminants that affects human health.